Merchant sail Volume 5 - Fairburn, William Armstrong (Center Lovell, Maine Fairburn Marine Educational Foundation, 1945)
United States wood shipbuilders and shipbuilding centers druing the days of the young republic and throughout the nineteenth century, with the production of sailing vessels, including packets, clippers, and down easter
65017
Keywords: History -- United States